Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menggunakan Metode SAW pada PT Hasta Bersama Prima Jaya Berbasis Java - Rini Prihartini; Ridwan Ridwan (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Employee Performance Assessment Decision Support System Using SAW Method at PT Hasta Bersama Prima Jaya Based on Java. The purpose of this study is to develop an existing employee performance assessment decision support system to facilitate data collection and employee performance assessment process. The research methodology used in the data processing system is the literature study method, namely data collection carried out by taking data from various books in the library, journals and other books that can be used as a basis for analyzing problems that can be discussed in the study, as well as the field study method, namely by conducting direct observations such as interviews and observations. The algorithm in solving the problem used is Simple Additive Weighting. The results of this study are the existence of an application device made with the Java programming language and data storage using a MySQL database so that the process of data collection and employee performance assessment at PT Hasta Bersama Prima Jaya becomes more effective, efficient and practical.